2007
DOI: 10.4049/jimmunol.178.8.4737
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Is Essential for the Development and the Persistence of Chronic Colitis

Abstract: Although IL-7 has recently emerged as a key cytokine involved in controlling the homeostatic turnover and the survival of peripheral resting memory CD4+ T cells, its potential to be sustained pathogenic CD4+ T cells in chronic immune diseases, such as inflammatory bowel diseases, still remains unclear. In this study, we demonstrate that IL-7 is essential for the development and the persistence of chronic colitis induced by adoptive transfer of normal CD4+CD45RBhigh T cells or colitogenic lamina propria (LP) CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 32 publications
7
82
0
Order By: Relevance
“…Furthermore, accumulating evidence suggests that IL-7 dependency is a reliable assumption for CD4 + memory T cells in vivo [31]. Consistently, we previously demonstrated that colitic LP CD4 + T cells from colitic CD4 + CD45RB high T cell-transferred RAG-2 -/-mice express representative cell surface markers of memory T cells such as IL-7Ra and CD44 at a high level, and that the IL-7 -/-Â RAG-1 -/-recipient mice transferred with CD4 + CD45RB high T cells or colitic LP CD4 + T cells never develop colitis [17].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Furthermore, accumulating evidence suggests that IL-7 dependency is a reliable assumption for CD4 + memory T cells in vivo [31]. Consistently, we previously demonstrated that colitic LP CD4 + T cells from colitic CD4 + CD45RB high T cell-transferred RAG-2 -/-mice express representative cell surface markers of memory T cells such as IL-7Ra and CD44 at a high level, and that the IL-7 -/-Â RAG-1 -/-recipient mice transferred with CD4 + CD45RB high T cells or colitic LP CD4 + T cells never develop colitis [17].…”
Section: Discussionsupporting
confidence: 74%
“…SCID mice transferred with such colitic LP CD4 + T cells (the second transfer) develop colitis similar to the original CD4 + CD45RB high T cell-transferred colitis in an IL-7-dependent manner [17]. This adoptive transfer model is also characterized by the rapid proliferation of donor CD4 + T cells by lymphopeniadriven proliferation [9,17], which provides an advantageous tool to assess the longevity and change in characteristics of these colitic LP CD4 + T cells during repetitive transfer into SCID mice (Fig. 1A).…”
Section: Incidence Of Colitis Is Gradually Decreased By Repeated Tranmentioning
confidence: 99%
See 2 more Smart Citations
“…To clarify this issue, splenic Ly5.1 + and Ly5.2 + CD4 + T cells from three groups were analyzed for their TCR Vb repertoire by three-color flow cytometry. It is reasonable to use SP CD4 + T cells in place of LP CD4 + T cells for this assay, since we previously demonstrated that colitic SP CD4 + T cells had similar characteristics in that they were CD4 + CD44 high CD62L -IL-7Ra high T EM -like cells [14], and were also colitogenic cells by which colitis can be transferred to new recipient mice [15]. As shown in Fig.…”
Section: Tcr Vb Repertoire Is Constant Between First and Second Transmentioning
confidence: 99%